From brand safety to suitability: Advertisers in platform governance - Rachel Griffin (Internet Policy Review, 2023)
Scholarship has long identified the business imperative to create an advertiser-friendly environment as a key influence on social media content moderation. However, "brand safety" - the industry term for advertisers' measures to avoid content perceived as reflecting negatively on their brands - remains understudied. Drawing on policy statements from industry actors, as well as extant academic literature, this article makes four contributions. First, it proposes four distinct mechanisms through which branding imperatives influence platforms' content governance. Second, it highlights two current trends: growing efforts by major advertisers to directly influence platforms' content policies, and a shift in industry terminology from brand safety (avoiding content widely considered objectionable) to "suitability" (evaluating appropriate content for a particular brand) - which promises advertisers greater customisation, but in fact promotes the standardisation of content governance across major platforms. Third, it explores the policy implications of these developments, in particular for equal participation and freedom of public debate on social media. Finally, it briefly explores the relevance to these concerns of the EU's 2022 Digital Services Act, suggesting that it fails to adequately address a marketised logic in which the production and distribution of online media content is increasingly shaped by what is deemed suitable for branding objectives.
Keywords: 300; Platform governance; Social media; Platform regulation; Content regulation; Digital Service Act